KONVERGENSI ANTARA RESTORATIVE JUSTICE DENGAN AL-'AFWU UNTUK PEMBARUAN HUKUM ACARA PIDANA DI INDONESIA: Reforming Criminal Procedure Law in Indonesia - Khamim, Khamim; Rizal, Moch. Choirul; Mustakim, Andi Ardiyan (Justicia Islamica, 2025)
The legal regulation on restorative justice in Indonesia, which allows for the forgiveness of perpetrators of criminal acts and the termination of their cases, is still limited to internal law enforcement regulations, not at the level of law, except in relation to the juvenile criminal justice system. The practice of this theoretically problematic regulatory model is feared to give rise to disparate practices in handling cases, which could undermine justice and legal certainty, making the renewal of criminal procedural law a necessity. Regarding this reason, this conceptual article explores the forgiveness of perpetrators of criminal acts through restorative justice, aiming to find common ground with the concept of al-‘afwu, as outlined in Islamic law, for the renewal of criminal procedural law in Indonesia. This article is included as socio-legal research, utilising a statutory, conceptual, and religious approach (Islamic legal studies). Its analysis is descriptive and prescriptive, drawing on primary and secondary legal materials collected and inventoried, particularly in relation to several emerging concepts regarding restorative justice and al-‘afwu. The research results found, First, legal regulations regarding the forgiveness of perpetrators of criminal acts need to be regulated in law. Second, it can only be applied to specific criminal acts. Third, forgiveness occurs when the victim or the victim’s family forgives. Fourth, forgiveness must be determined by a judge. Fifth, forgiveness does not eliminate the perpetrator’s criminal liability, but it can reduce or mitigate the punishment.